High-Normal Preconception TSH Levels Have No Adverse Effects on Reproductive Outcomes in Infertile Women Undergoing the First Single Fresh D5 Blastocyst Transfer - Yuchao Zhang; Wenbin Wu; Yanli Liu; Yichun Guan; Xingling Wang; Liting Jia (International Journal of Endocrinology)
Purpose. To investigate the association between high-normal preconception TSH levels and reproductive outcomes in infertile women undergoing the first single fresh D5 blastocyst transfer. Methods. This was a retrospective study. Euthyroid patients undergoing the first single fresh D5 blastocyst transfer from January 2018 to May 2019 were initially included. The patients were divided into a low TSH (0.27–2.5 mIU/L) group and a high-normal TSH (2.5–4.2 mIU/L) group. The reproductive outcomes were compared between the groups. Results. A total of 824 women were ultimately included, 460 of whom had serum TSH levels less than 2.5 mIU/L and 364 of whom had serum TSH levels between 2.5 and 4.2 mIU/L. The patients were highly homogeneous in terms of general characteristics. High-normal TSH levels had no adverse impact on the clinical pregnancy rate, miscarriage rate, or live birth rate (respectively, aOR = 0.84, 0.65, 0.61, and P=0.234, 0.145, 0.083). No significant differences were observed in terms of gestational age, single live birth rates, birth weight, or birth length. Conclusion. High-normal TSH levels did not significantly influence reproductive outcomes in infertile women undergoing the first single fresh D5 blastocyst transfer. Further studies are needed to test whether the results might be applicable to a wider population.